Response surface methodology assessment of osmotic pre-drying and convective dehydration processes on the anti-oxidant property of Hausa variety of tomato - Obajemihi, Obafemi Ibitayo (Array, 2019)
This study was conducted to determine the effect of osmotic pre-drying treatment on the vitamin C content of Hausa variety of tomato. The tomatoes used were sliced to a uniform diameter of 10 mm, deseeded and then osmotically pre-treated with sugar and honey solution at different osmotic concentrations (20, 30, 40, 50, 60 °Bx), osmotic time (10, 20, 30, 40 and 50 min) and osmotic temperature (10, 20, 30, 40, 50 °C). Experimental design was done using the Central Composite Design (CCD) methodology of Design Expert software version 6.0.6. Drying of the samples was done at 65 °C in a cabinet dryer operating mainly on convectional heat transfer. Drying process was completed and terminated when the samples reached their equilibrium moisture content between 3-5% after total drying time of 10 hours. The data obtained were analysed statistically using analysis of variance (ANOVA) and regression analysis at p≤0.05 significance level. The developed model was significant and has goodness of fit with an R2 value of 71.29% and lack of fit test was insignificant at p≤ 0.05. Optimized process conditions for producing the best quality of tomato product with vitamin C content of 22 mg/100 g were 35.43 °Bx osmotic concentration, 11.10 min osmotic time and 23.86 °C osmotic temperature having a desirability function of 1. These conditions were considered to be advantageous as they were more economical, time and energy saving.